2013
DOI: 10.1002/ejoc.201301293
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Direct Dehydroxylation of Alcohols

Abstract: Iridium‐catalyzed direct dehydroxylation of alcohols with hydrazine was developed through a combination of the oxidation of alcohols and the Wolff–Kishner reduction. This protocol is simple to perform and highly efficient for a series of primary, benzylic and allylic alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…It has previously been observed that Vaska's complex does not dehydrogenate an alcohol without the presence of a strong base. 34 These results again illustrate that monodentate phosphine ligands are less effective in the dehydrogenation cycle.…”
Section: The Effect Of Licl and H 2 Omentioning
confidence: 83%
“…It has previously been observed that Vaska's complex does not dehydrogenate an alcohol without the presence of a strong base. 34 These results again illustrate that monodentate phosphine ligands are less effective in the dehydrogenation cycle.…”
Section: The Effect Of Licl and H 2 Omentioning
confidence: 83%
“…For example, benzyl alcohol was reduced in 54% yield after 3 h using Pd/C catalyst in compressed CO 2 /water and 1 MPa H 2 [4]. Independently, Huang et al [5] obtained toluene in 98% yield through the reduction of benzyl alcohol using iridium catalyst with hydrazine at 160°C after 3 h. Wang et al [6] reported benzyl alcohol hydrogenolysis in 99% yield using PdCl 2 and PMHS after 12 h at 40°C.…”
Section: Catalytic Performances Of Pd Nps/rgomentioning
confidence: 96%
“…It should be noted that this procedure allowed the reduction of benzyl alcohol derivatives in relatively short reaction times and mild conditions as compared to the methods described in the literature [4][5][6]. For example, benzyl alcohol was reduced in 54% yield after 3 h using Pd/C catalyst in compressed CO 2 /water and 1 MPa H 2 [4].…”
Section: Catalytic Performances Of Pd Nps/rgomentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, we have disclosed a ruthenium-catalyzed deoxygenation reaction for the highly selective cleavage of aliphatic primary C–O bonds. 10 Building on the similar ruthenium( ii ) catalysis, we further demonstrated its robustness in catalyzing a series of new carbon–carbon bond forming processes through addition reactions to various carbonyl compounds, imines and activated alkenes. 11 13 Variations of these precedents notwithstanding, one of their commonalities is to use aldehydes/ketones as alkyl carbanion equivalents via hydrazone formation.…”
mentioning
confidence: 95%